Polish «traces» of Ukrainian Narodnik movement at the turn of 1850–1860s - Prysyazhnyuk, J.; Shamara, S.; Ignatenko, J. (Вісник Черкаського університету. Серія: Історичні науки, 2016)
Introduction. In their reasoning the authors followed the hypothesis that quite clearly Polish motives (destructive or creative) began to occur around intellectual activity of khlopomans just at the turn of 1850–1860s. Later they will be formatted in Ukrainian style and widely enough, that is socially, geographically, temporally. Purpose. The aim is to show the Polish component of the Ukrainian Narodnik movement (love for the people) in its destructive and constructive perspectives. Methods. The research methodology is based on local social history, that is behavioral strategies of khlopomans are given in the context of social and partially ideological public regulators. Results. At the turn of 1850–1860s the formation of the Ukrainian Narodnik movement took place. The process was connected with the transformation of the part of the Polish intelligentsia into the Ukrainian national-cultural environment. To a large extent this circumstance determined the essence of this historical phenomenon. Originality. The Khlopomans knew that peasants were apolitical, so they did not have much hope for their participation in the political movement. Actually, because of this fact they directed their activities primarily on mass education, development and improvement of national ideology. Thus, they certified their understanding of the perspectives of the modern era, which absorbed the sphere of thought and creativity, the community rather than individuals became central, they were in search of heroes that were designed to liberate the people, to show them the way to stability and prosperity. <span lang="EN-US" style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusion<span lang="EN-US" style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;">. The Polish <span lang="UK" style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: UK; mso-fareast-language: RU; mso-bidi-language: AR-SA;">«<span lang="EN-US" style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;">traces<span lang="UK" style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: UK; mso-fareast-language: RU; mso-bidi-language: AR-SA;">»<span lang="EN-US" style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;"> of the Ukrainian Narodnik movement is primarily the result of the total fascination with the ideas of the Enlightenment, liberal reforms, utopian socialism and other areas of social and political thought which were integrated from France, Germany and other European countries often through the Polish perspective. Nevertheless, the Ukrainian Narodnik movement was fundamentally different from the Polish national competition with the rejection of aristocracy and a broader, though less elitist social base.